Quantification of leaching kinetics in OPC mortars via a mesoscale model. (20th August 2018) - Seetharam, S.C.; Patel, R.A.; Perko, J.; Jacques, D.
Highlights: A new 3D computational mesoscale framework to address calcium leaching kinetics. Captures the effect of aggregates and interface transition zone (ITZ) on leaching kinetics. Confirms the opposing influence of aggregates and ITZ in leaching kinetics. Abstract: The problem of calcium leaching kinetics of ordinary Portland cement based mortars is revisited via a mesoscale approach. Based on state-of-the-art lattice-Boltzmann technique, a comprehensive suite of leaching analysis is undertaken to address a number of open questions such as (i) the competing effects of interface transition zone (ITZ) and aggregates, (ii) relative leaching rates of calcium between ITZ and mortar cement paste, and (iii) the influence of different water to cement ratios, volume fraction of aggregates and hence of ITZ on leaching kinetics. The mesoscale model is not only able to correctly reproduce experimentally observed trends but also confirm the commonly accepted hypothesis that ITZ and aggregates counter-balance their effect leading to similar portlandite leaching rates in cement paste and mortars. The model also confirms the applicability of simple scaling approach for upscaling leaching kinetics from pure cement paste to mortar scale under the condition that ITZ is fully percolated.